Tata Laksana Pemeliharaan Ayam Cemani Di Peternakan NF Temanggung Jawa Tengah - I K Habsari; B A Nugroho; S Azizah (Politeknik Negeri Lampung, 2019)
This study was aimed to observe rearing management of cemani chicken in NF Farm, Temanggung, Central Java. NF Farms was chosen purposively due to the high population. Data collection techniques using observation techniques, direct observation of maintenance management which includes cage and chicken feed cemani. The result showed that Cemani chickens in grower period used battery cage 120 x 60 cm2 for 2-3 chickens in each cage, while in layer period used litter cage 6x4 m2 and each cage consisted of 1 male and 5 female cemani chicken. Feeding management NF farm for 1-3 days old were only given drinking water added by palm sugar. 3- 40 days old Cemani chickens were fed 511 given 25-30 g/bird/day with 22% protein content and 3,050 kkal/kg energy. Whereas for the grower period feed is divided into two, at the age of 41-75 days, chickens are fed with BR 1 and corn ratio 1:1, andÂ for 76 days- 6 months old, they are fed with ground corn, bran and BR 1 with the ratio 1: 1 : 1 as much as 80 g / head / day.Â Keywords: Cemani, Rearing management, Feeding